The Correlation between Intrinsic Motivation and Speaking Proficiency of the English Department Students. - Aventia Wilona; Agustinus Ngadiman; M.G. Retno Palupi (Magister Scientiae, 2010)
The purpose of the research was to find out whether there is a correlation between intrinsic motivation and speaking proficiency. The correlation research was conducted with the assistance of a motivational questionnaire and speaking proficiency level as the instruments. Twenty nine respondents, who were the students of the English Department of Widya Mandala Catholic University Surabaya, participated in the research. They took part in filling out the questionnaire and giving out their recent Speaking Class grade. The data gathered were soon correlated using Spearman’s Rank Correlation Coefficient formula. The findings show that there is a moderate correlation between intrinsic motivation and speaking proficiency. Having Intrinsic Motivation in the process of learning a foreign/second language helps people to achieve better speaking proficiency. And through the research, the writer suggests that motivation is indeed an important factor for the success of language learning and acquisition in all aspects and skills; therefore, educators and learners should perceive the importance of being intrinsically motivated. The writer also suggests that in the future time, there should be deeper researches regarding the types of motivation, as well as the orientations of motivation.